2021
DOI: 10.5114/biolsport.2021.99702
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of readiness and perceived workload in junior female basketball players during a congested match schedule

Abstract: This study aimed to: a) investigate the differences in workload and readiness between two junior female national basketball teams competing at different European Championships (EC); b) compare workload, readiness and match performance for players with longer and shorter playing times, and; c) examine the relationship between workload, readiness and match performance variables. Under-18 (U18) (n = 10, height = 179.9 ± 6.6 cm, body mass = 70.2 ± 5.1 kg) and under-20 (U20) female national basketball teams (n = 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
2
7
0
1
Order By: Relevance
“…Similarly, Clemente et al (2019) also concluded that weeks with two matches presented moderately greater fatigue (p = 0.47; d = 1.40, moderate effect) and lower sleep quality (p = 0.42; d = 1.32, moderate effect) than weeks with one match. Despite these results, basketball players can apparently cope with different types of congested match schedules after the failure to detect significant differences in training load, readiness, and recovery status (Clemente et al, 2019;Pino-Ortega et al, 2019;Fox et al, 2020;Lukonaitiene et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, Clemente et al (2019) also concluded that weeks with two matches presented moderately greater fatigue (p = 0.47; d = 1.40, moderate effect) and lower sleep quality (p = 0.42; d = 1.32, moderate effect) than weeks with one match. Despite these results, basketball players can apparently cope with different types of congested match schedules after the failure to detect significant differences in training load, readiness, and recovery status (Clemente et al, 2019;Pino-Ortega et al, 2019;Fox et al, 2020;Lukonaitiene et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Overall, this outcome might indicate a likely negative correspondence between the sRPE-load and well-being values. However, previous literature documented a negative, small (rho = −0.150) relationship between sRPE-load calculated during matches performed across a European championship in youth female basketball players, and the well-being measured in the following morning [ 18 ]. Overall, considering our outcomes and those reported in previous literature [ 18 ], it seems important for basketball practitioners to monitor both load and well-being across various parts of the season due to their small relationship.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous literature documented a negative, small (rho = −0.150) relationship between sRPE-load calculated during matches performed across a European championship in youth female basketball players, and the well-being measured in the following morning [ 18 ]. Overall, considering our outcomes and those reported in previous literature [ 18 ], it seems important for basketball practitioners to monitor both load and well-being across various parts of the season due to their small relationship. It also seems important to investigate further the relationships between load and well-being across different times of the seasons and different basketball populations, which might provide useful indications for practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…While this evidence is important from a practical standpoint to identify the main match load measures affecting post-match perceived well-being [5], the assessment of the relationships between pre-match well-being and match loads could also provide further insight for women's rugby sevens practitioners about players' capacity to perform matches based on previous well-being values. Previous studies across various team sports mainly assessed the effect of well-being on training sessions rather than on match performance [15][16][17][18][19]. Specifically, a negative effect of pre-training perceived well-being on external load measures in Australian football players [15] and on internal perceived training load in professional male soccer [16] as well as female volleyball players [19].…”
Section: Discussionmentioning
confidence: 99%